Impact of Dentofacial Deformity on Quality of Life: Age and Gender Differences Evaluated Through OQLQ, OHIP and SF36 - Marcelo Carlos Bortoluzzi; Priscila de Camargo Smolarek; Marcela Claudino; Eduardo B. Campagnoli; Rafael Manfro (eJournal of Oral Maxillofacial Research)
Objectives: The aim of this study was to verify the impact of dentofacial deformity on quality of life and explore gender and age differences.